2007
DOI: 10.1597/06-011.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking during Early Pregnancy, GSTP1 and EPHX1 Variants, and Risk of Isolated Orofacial Clefts

Abstract: Our results suggest that genetic variation of the detoxification enzymes EPHX1 and GSTP1 did not increase the risks of orofacial clefting, nor do they influence the risks associated with maternal smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Hartsfield et al (2001) found no association between the fetal Y113H polymorphism in EPHX1 with maternal smoking and oral clefting. Negative results were also reported by Ramirez et al (2007), who performed a study based on a larger set of samples. Shi et al (2007) however did find a significant interaction effect between the EPHX1 Y113H variant in the fetus and maternal smoking on oral clefts in an Iowan population.…”
Section: Epoxide Hydrolasementioning
confidence: 79%
See 1 more Smart Citation
“…Hartsfield et al (2001) found no association between the fetal Y113H polymorphism in EPHX1 with maternal smoking and oral clefting. Negative results were also reported by Ramirez et al (2007), who performed a study based on a larger set of samples. Shi et al (2007) however did find a significant interaction effect between the EPHX1 Y113H variant in the fetus and maternal smoking on oral clefts in an Iowan population.…”
Section: Epoxide Hydrolasementioning
confidence: 79%
“…This suggests that variable GSTP1 expression may be an important determinant of susceptibility to environmental chemicals. Significant interaction between offspring GSTP1 and maternal smoking for CL/P was reported by Shi et al (2007), but this interaction effect was not found by Ramirez et al (2007). Shi et al (2007) also studied two other members of the GST family, GSTA4 and GSTM3, and reported significant interaction between offspring GSTA4 and maternal smoking for CPO in a Danish population.…”
Section: Glutathione Transferase Gene Familymentioning
confidence: 99%
“…22 GSTP1 is important in the detoxification of toxic compounds present in tobacco smoke. 23 Just recently, Ramirez et al 24 and Shi et al 25 could not find an association between the GSTP1 I105V polymorphism and CL/P. However, in their unadjusted Danish data, they showed a two-fold increased CL/P risk in homozygous I105V foetuses with a smoking mother.…”
Section: Introductionmentioning
confidence: 92%
“…Compared to that review, this one has included 20 additional studies 6,7,8,9,10,11,12,13,14,24,43,79,83,95,99,102,103,122,125,188 that have added about 10,000 cases of defects, and 800,000 of controls. Another difference between the two reviews is that 19 studies about abdominal wall defects were included in the meta-analysis of the gastro-intestinal system in the previous review, whereas these defects were classified as pertaining to the musculoskeletal system in this review.…”
Section: Discussionmentioning
confidence: 99%
“…While this investigation was being carried out, a systematic review with 101 observational studies was published, and showed an association between maternal smoking during pregnancy and different birth defects in children 5 . This review, however, did not include a considerable number of relevant studies 6,7,8,9,10,11,12,13,14 . Moreover, defects of the abdominal wall, such as congenital diaphragmatic and inguinal hernia, gastroschisis, and omphalocele, which should be considered musculoskeletal abnormalities, according to the 10 th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) 15 were classified as gastrointestinal defects.…”
Section: Introductionmentioning
confidence: 99%